Analysis of Strength and Durability Of Road Pavement with Stell Slag and Natural Aggregate: A Promising Solution for Sustainable Road Construction (Journal of Advances and Scholarly Researches in Allied Education, 2023)
Steel slag is a by product from steelmaking industry and has been recycled in many countriesaround the world for decade. One of the main application of the recycled steel slag is aggregate for asphaltpavement. This particle aims to present an overview of the application of steel slag in the pavementindustry covering the regulation in different parts of the world that govern the reuse of steel slag ,how theproperties of steel slag influence the strength and durability of the pavement mixtures, and theenvironmential impact as a result of the reuse of steel slag. This article elaborates on supply chainmanagement issues in steel slag recycling industry, as the quality of steel slag relies not only on thetreatment and processing technique but also the way the material are handled throughout their lifetime.This study is evaluates the used of steel slag aggregate in the proportion(SSA) as a substitute for naturalaggregate in the production of hot mix plant(HMA) for road construction. Based on intensive laboratorytesting program the the characteristic properties of SSA were assessed to determine its suitability to beused HMA. (Four different percentages (0, 50, 75, and 100) of SSA were used, and the proposed mixdesigns for HMA were conducted in accordance with Marshall mix design. The experiment resultsrevealed that the addition of SSA has a significant improvement on the properties natural aggregate. Anincrease in density and stability and a reduction in flow and air voids values were clearly observed inspecimens prepared with 100 SSA. It is concluded that the steel slag can be considered reasonablealternative source of aggregate for road construction